Stocktaking of the Housing Sector in Sub-Saharan Africa : Challenges and Opportunities - World Bank Group (World Bank, Washington, DC, 2015)
Africa is rapidly urbanizing and will lead the world’s urban growth in the coming decades. Currently, Africa is the least‐urbanized continent, accommodating 11.3 percent of the world’s urban population, and the Sub‐Saharan region is the continent’s least‐urbanized area. However, the region’s cities are expanding rapidly, by 2050; Africa’s urban population is projected to reach 1.2 billion, with an urbanization rate of 58 percent (UN‐HABITAT 2014). With this rate of growth, Africa will overtake Asia as the world’s most rapidly urbanizing region by 2025 (UN 2014). Although the nature and pace of urbanization varies among countries, with over a quarter of the world’s fastest growing cities, Africa is undergoing a massive urban transition. Globally, cities are major drivers of economic growth, and the quality and location of housing has long-term consequences for inclusive growth. However, in Sub-Saharan Africa, urbanization is not accompanied by the level of per-capita economic growth or housing investment that is observed elsewhere in global trends. Incomes in Sub‐Saharan Africa (SSA) have not kept pace with urbanization, which, in many African countries, has not necessarily been accompanied by industrial growth and the structural transformation as has occurred in other regions. Housing stocks, along with investment and employment in related construction and finance industries, constitute a major component of national economic wealth. The key challenge for African cities, however, has been the comparatively low growth in per‐capita income, which limits the resources that households have to consume or invest in housing. At the same time across the region, the formal channels through which quality housing is produced and financed face major constraints that limit access to a large share of urban households. Hence, the formal housing sector is only a small part of the economy because the construction and finance services have very little effective demand, evidenced by the lack of formal investment in housing across the region. Recent studies have found that in Africa, formal housing investment (in national current accounts data) lags behind urbanization by nine years (Dasgupta et al. 2014). Furthermore, the capital investment in infrastructure needed to handle rapid urbanization typically happens (if at all) after housing has already been built, often in informal settlements.